EARTH TIDES AS A TECTONIC PUMP AND VIBRATOR - Shilo N.A.; Vashchilov Yu.Ya. (My University, 1989)
Vertical displacements of the solid surface of the earth resulting from lunar-solar high and low tides are asymmetrical relative to the zero position, in that the amplitudes of the high tides are greater than those of the low tides. In addition, in the vicinity of the tidal hump, pores and cracks are generated and expand as a result of an increase in the volume of solid matter. This is why the water level falls in wells on continents during tides. But in tectonomagmatically active areas the tides 'open' quasiclosed magma chambers, resulting in the ascent of melts and most importantly, of vapors and gases, after which, during the semidiurnal low tide, the chamber close again. Thus the tides may be regarded as a unidirectional 'tectonic pump' and as a catalyst for progressive polymorphic conversion of the plutonic matter at the boundary between the solid and liquid phases. Thus the moon activates tectonic processes in the earth. The fact that Venus, Mars and Mercury lack such a large moon is the reason for the apparent inapplicability of the energy-intensive mechanism of plate tectonics to the other planets.